Quantifying the evolution of a scientific topic: reaction of the academic community to the Chornobyl disaster - Mryglod, O.; Holovatch, Yu; Kenna, R.; Berche, B. (Scientometrics, 2016)
We analyze the reaction of academic communities to a particular urgent topic which abruptly arises as a scientific problem. To this end, we have chosen the disaster that occurred in 1986 in Chornobyl (Chernobyl), Ukraine, considered as one of the most devastating nuclear power plant accidents in history. The academic response is evaluated using scientific-publication data concerning the disaster using the Scopus database to present the picture on an international scale and the bibliographic database “Ukrainika naukova” to consider it on a national level. We measured distributions of papers in different scientific fields, their growth rates and properties of co-authorship networks. Elements of descriptive statistics and tools of complex network theory are used to highlight the interdisciplinary as well as international effects. Our analysis allows comparison of contributions of the international community to Chornobyl-related research as well as integration of Ukraine in international research on this subject. Furthermore, the content analysis of titles and abstracts of the publications allowed detection of the most important terms used for description of Chornobyl-related problems.